Debt, recovery rates and the Greek dilemma - Goodhart, C; Peiris, M; Tsomocos, D (Elsevier, 2018)
Most discussions of the Greek debt overhang have focussed on the implications for Greece. We show that when additional funds released to the debtor (Greece), via debt restructuring, are used efficiently in pursuit of a practicable business plan, then both debtor and creditor can benefit. We examine a dynamic two country model calibrated to Greek and German economies and support two-steady states, one with endogenous default and one without, depending on creditors’ expectations. In the default steady state, debt forgiveness lowers the volatility of both German and Greek consumption whereas demanding higher recovery rates has the opposite effect. In a second order approximation of the model, conditional welfare analysis shows that a policy of immediate leniency followed by harsher terms as the economy grows is beneficial to both creditors and debtors.